Intestinal Epithelial Organoids as Tools to Study Epigenetics in Gut Health and Disease - Judith Kraiczy; Matthias Zilbauer (Stem Cells International)
The intestinal epithelium forms the inner layer of the human intestine and serves a wide range of diverse functions. Its constant exposure to a vast amount of complex microbiota highlights the critical interface that this single-cell layer forms between the host and our environment. Importantly, the well-documented contribution of environmental factors towards the functional development of the human intestinal epithelium directly implies epigenetic mechanisms in orchestrating this complex interplay. The development of intestinal epithelial organoid culture systems that can be generated from human tissue provides researchers with unpresented opportunities to study functional aspects of human intestinal epithelial pathophysiology. In this brief review, we summarise existing evidence for the role of epigenetics in regulating intestinal epithelial cell function and highlight the great potential for human gut organoids as translational research tools to investigate these mechanisms in vitro.